Macros to Quantify Exosome Release and Autophagy at the Neuromuscular Junction of Drosophila Melanogaster - Sanchez-Mirasierra, Irene; Hernandez-Diaz, Sergio; Ghimire, Saurav; Montecinos-Oliva, Carla; Soukup, Sandra-Fausia (Frontiers in Cell and Developmental Biology, 2021)
Automatic quantification of image parameters is a powerful and necessary tool to explore and analyze crucial cell biological processes. This article describes two ImageJ/Fiji automated macros to approach the analysis of synaptic autophagy and exosome release from 2D confocal images. Emerging studies point out that exosome biogenesis and autophagy share molecular and organelle components. Indeed, the crosstalk between these two processes may be relevant for brain physiology, neuronal development, and the onset/progression of neurodegenerative disorders. In this context, we describe here the macros “Autophagoquant” and “Exoquant” to assess the quantification of autophagosomes and exosomes at the neuronal presynapse of the Neuromuscular Junction (NMJ) in Drosophila melanogaster using confocal microscopy images. The Drosophila NMJ is a valuable model for the study of synapse biology, autophagy, and exosome release. By use of Autophagoquant and Exoquant, researchers can have an unbiased, standardized, and rapid tool to analyze autophagy and exosomal release in Drosophila NMJ.